Pengaruh Transformasi Digitalisasi Akuntansi dan Literasi Keuangan terhadap Kinerja Keuangan UMKM di Kabupaten Jember - Helinda Kiki Octaviana; Gardina Aulin Nuha; Ibna Kamelia Fiel Afroh (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2026)
This study aims to determine the effect of accounting digital transformation and financial literacy on the financial performance of MSMEs in Jember Regency by 2025. MSMEs were selected because they play a crucial role as the main foundation of the national economy, including Jember Regency. However, accounting digital transformation and financial literacy are factors suspected of improving MSME financial performance. This study used a quantitative approach with a survey method through the distribution of questionnaires to 111 MSMEs in Jember Regency. The data analysis technique used was multiple linear regression, involving control variables consisting of education level, gender, length of business, and type of business. The results showed that accounting digital transformation had a positive and significant effect on MSME financial performance. Financial literacy was also shown to have a positive and significant effect on MSME financial performance. Furthermore, accounting digital transformation and financial literacy simultaneously had a significant effect on MSME financial performance, while the control variables showed no significant effect. The results of this study illustrate that improving MSME financial performance can be supported through the use of digital technology balanced with sound financial management skills